The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1116/1.2375084
|View full text |Cite
|
Sign up to set email alerts
|

Thin membrane self-alignment using nanomagnets for three-dimensional nanomanufacturing

Abstract: Articles you may be interested inGrazing incidence X-ray scattering showing self-organized regular three-dimensional nanopillar-like structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…In recent work, Nichol et al demonstrated that arrays of nanomagnets can be used to align folding membranes to each other to the order of 200 nm [2]. Using a similar technique, we propose to align and attach the free ends of plasma enhanced chemical vapor deposition (PECVD) grown multiwalled carbon nanotubes (MWCNTs) onto corresponding magnetic receptor sites as well as to each other.…”
Section: Magnetic Alignmentmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent work, Nichol et al demonstrated that arrays of nanomagnets can be used to align folding membranes to each other to the order of 200 nm [2]. Using a similar technique, we propose to align and attach the free ends of plasma enhanced chemical vapor deposition (PECVD) grown multiwalled carbon nanotubes (MWCNTs) onto corresponding magnetic receptor sites as well as to each other.…”
Section: Magnetic Alignmentmentioning
confidence: 94%
“…The magnetic attraction force between a CNT tip and a magnetic attachment site located approximately 100 nm from the tip can be estimated in a similar fashion as for nanomagnet arrays [2] …”
Section: 1alignment Theorymentioning
confidence: 99%
“…The finite length of the creases imparts additional separation between adjacent facets that are neglected in the present formulation. An experimental solution to this problem is to further thin the creases and employ a fine alignment technique using nanomagnets [18].…”
Section: A Geometrymentioning
confidence: 99%
“…According to the reported results, there are some successful examples of magnetic polymers. Barbastathis et al [22,23] obtained membranes patterned with arrays of nanomagnets by e-beam evaporation and optical lithography. The as-prepared membranes can be folded and coarsely aligned in magnetic field.…”
Section: Introductionmentioning
confidence: 99%